A technology ecosystem perspective on hospital management information systems: lessons from the health literature. (11th November 2009) - Bain, Christopher A.; Standing, Craig
Hospital managers have a large range of information needs including quality metrics, financial reports, access information needs, educational, resourcing and decision support needs. Currently these needs involve interactions by managers with numerous disparate systems, both electronic such as SAP, Oracle Financials, PAS' (patient administration systems) like HOMER, and relevant websites; and paper-based systems. Hospital management information systems (HMIS) can be thought of sitting within a Technology Ecosystem (TE). In addition, Hospital Management Information Systems (HMIS) could benefit from a broader and deeper TE model, and the HMIS environment may in fact represents its own TE (the HMTE). This research will examine lessons from the health literature in relation to some of these issues, and propose an extension to the base model of a TE.